Short Chain Fatty Acids Protect the Cognitive Function of Sepsis Associated Encephalopathy Mice via GPR43 - Liao, Hongsen; Li, Haojia; Bao, Hongguang; Jiang, Li; Du, Jiayue; Guo, Yaoyi; Si, Yanna (Frontiers in Neurology, 2022)
Objective: To analyze the changes of fecal short chain fatty acids (SCFAs) content and gut microbiota composition in sepsis associated encephalopathy (SAE) mice, further evaluating the effect of SCFAs on cognitive function and the underlying mechanism in SAE mice. Methods: A total of 55 male adult C57BL/6 mice (2-3 months of age, 20-25g) were divided into four groups randomly: sham group (n=10), cecal ligation and puncture group (CLP group, n=15), CLP+SCFAs group (n=15) and CLP+SCFAs+GLPG0974 group (n=15). Seven days after surgery, fecal samples were collected for microbiota composition and SCFA analysis from 6 mice in each group randomly. Behavioral test was applied to assess cognitive impairment at the same time. After that, mice were sacrificed and brain tissue was harvested for inflammatory cytokines analysis. Results: The levels of acetic acid (0.57±0.09 vs 2.00±0.24, p<0.001) and propionic acid (0.32±0.06 vs 0.66±0.12, p=0.002) were significantly decreased in CLP group compared with sham group. The administration of SCFAs significantly increased the levels of acetic acid (1.51±0.12 vs 0.57±0.09, p<0.001) and propionic acid (0.54±0.03 vs 0.32±0.06, p=0.033) in CLP+SCFAs group compared with CLP group. Relative abundance of SCFAs-producing bacteria, including Allobaculum (0.16±0.14 vs 15.21±8.12, p=0.037), Bacteroides (1.82±0.38 vs 15.21±5.95, p=0.002) and Bifidobacterium (0.16±0.06 vs 2.24±0.48, p=0.002), significantly decreased in CLP group compared with sham group. The behavioral tests suggested that cognitive function was impaired in SAE mice, which could be alleviated by SCFAs pretreatment. ELISA tests indicated that the levels of IL-1β, IL-6 and TNF-α were elevated in SAE mice and SCFAs could lower them. However, the GPR43 antagonist GLPG0974 could reverse the cognitive protective effect and anti-neuroinflammation effect of SCFAs. Conclusion: Our study suggested that in SAE, the levels of acetate and propionate decreased significantly, accompanied by gut microbiota dysbiosis, particularly a decrease in SCFAs-producing bacteria. GPR43 was essential for the anti-neuroinflammation and cognitive protective effect of SCFAs in SAE.